A new hyperchaotic temperature fluctuations model, its circuit simulation, FPGA implementation and an application to image encryption. (2018) - Vaidyanathan, Sundarapandian; Azar, Ahmad Taher; Rajagopal, Karthikeyan; Sambas, Aceng; Kacar, Sezgin; Cavusoglu, Unal
In this paper, we propose a new hyperchaotic temperature fluctuations model and describe its modelling in detail. We study the characteristics of the new hyperchaotic temperature fluctuations model such as its phase portraits, rest points, symmetry, invariance, Lyapunov characteristic exponents, bifurcation analysis, etc. In fact, it is shown that the new temperature fluctuations model has a self-excited, two-scroll, hyperchaotic attractor with complex properties. The circuit simulation of the new temperature fluctuations model is carried out in MultiSim to verify the feasibility of the theoretical model. In addition, FPGA implementation of the new hyperchaotic temperature fluctuations model is also presented. An engineering application of the new hyperchaotic temperature fluctuations model for image encryption has been also described.